(untitled) (Research, Society and Development, 2023)
Objective: Deepening studies to elucidate the scenario of Psychosocial Care for children and adolescents and their families in Brazil. Methodology: A systematic integrative review was carried out of the literature indexed in a journal with a classification equal to or greater than B2, according to the evaluation of WebQualis (2014), between 2018 and 2022 in the databases of the Virtual Health Library (BIREME) and SCIELO (Scientific Electronic Library Online). Published articles should be in Portuguese, in full and available online, for the health area and describe practices in psychosocial care for children and adolescents and their families. Results and Discussion: It was found that all articles bring the need for greater intersectoriality in psychosocial care practices, especially when the target audience is children, adolescents and their guardians. As well as the model of care provided to this population. Conclusion: The results point to a greater concern in the intersectoral and multidisciplinary field, given the complexity of the subject. In view of the above, it is important that care for family members is provided through dialogue, respecting their psychological, social and spiritual dimensions, helping to provide humanized care.